The First Men on the Moon The Story of Apollo 11 - Harland, David M. (Space Exploration, 2007)
On 12 April 1961 Yuri Gagarin became the first man to orbit the Earth. One month later, President John F. Kennedy challenged the American nation to land a man on the Moon before the decade was out. On 16 July 1969, Neil Armstrong, Michael Collins and Buzz Aldrin set off in Apollo 11 to attempt this audacious mission, and succeeded magnificently. This book tells the story of Apollo 11, starting with crew selection and training, the choice of the landing site, and the assembly of the space vehicle, then a detailed account of the mission, featuring the lunar landing and moonwalk, and a review of how our knowledge of the Moon's history was revolutionised as a result. The story is enlivened by dialogue between the astronauts in space and the flight controllers in Mission Control.